Assessing cultural competency among Canadian chiropractors: a cross-sectional survey of Canadian Chiropractic Association members - Nora Bakaa; Danielle Southerst; Pierre Côté; Luciana Macedo; Lisa C. Carlesso; Joy MacDermid; Silvano Mior (Chiropractic & Manual Therapies, 2023)
Abstract Background There is a paucity of research assessing cultural competency among Canadian chiropractors. Therefore, the aims of this study were to (1) measure cultural competency among Canadian chiropractors, (2) understand chiropractors’ perspectives of challenges and attitudes regarding the delivery of chiropractic services to equity-seeking communities, and (3) assess contextual factors associated with cultural competency. Methods We conducted a cross-sectional survey of members of the Canadian Chiropractic Association (CCA) (May–July 2021). The survey instrument consisted of 57 questions related to demographics, cultural competency, perceptions about health disparities, and challenges in delivery of rehabilitation. Cultural competency was measured using the Cultural Awareness and Sensitivity and Cultural Competence Behaviours subscales of the Cultural Competence Assessment Instrument. We conducted a multivariate linear regression to assess factors that may be associated with cultural competency. Results A total of 3143 CCA members responded (response rate of 41%). Mean scores for the Cultural Awareness and Sensitivity subscale were 5.8/7 (95% CI 5.7; 5.8) and 4.2/7 (95% CI 4.1; 4.2) for the Cultural Competence Behaviour subscale. Most chiropractors (72–78%) reported observing important cultural health disparities across various care-related outcomes. Cost of services and language were identified as barriers to providing care to equity-seeking communities. Cultural Awareness and Sensitivity scores were weakly associated with gender (men), years of clinical practice, cultural health disparities, the statement “I think some people have an agenda to look for discrimination even where it does not exist (DEI attitudes),” race (Caucasian), and prior DEI training, (R2 = 0.15, p < 0.0001). Cultural Competence Behaviour scores were weakly associated with race (Caucasian), cultural health disparities, prior DEI training, increased years of clinical experience, and higher Cultural Awareness and Sensitivity scores (R2 = 0.19, p < 0.0001). Conclusion This study provides the first description of cultural competency within the chiropractic profession in Canada. Findings suggest a gap between knowledge and behaviour and uncover several barriers and challenges that may inform the development of profession-specific training in cultural competence.